2021
DOI: 10.13057/biodiv/d220622
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: The resistance of Styrax sumatrana wood of varying growth sites and stem axial positions to subterranean termite (Coptotermes curvignathus) attack

Abstract: Abstract. Iswanto AH, Tambunan J, Susilowati A, Hartono R, Darwis A. 2021. Short Communication: The resistance of Styrax sumatrana wood of varying growth sites and stem axial positions to subterranean termite (Coptotermes curvignathus) attack. Biodiversitas 22: 3192-3198.  As mega-biodiversity country, Indonesia consists of a large number of flora and fauna, including wood-destroying organisms such as termites.  One of the native trees known as a resin producer is Tobanese incense (Styrax sumatrana). The exist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Concerning human life, termites are considered as insects that destroy wood or derivative products made from wood. Several studies related to the resistance of wood and non-wood lignocellulosic materials have been carried out by researchers, including [6][7][8][9]. Termite attacks are a risk for particleboard, a composite product consisting of lignocellulosic material.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning human life, termites are considered as insects that destroy wood or derivative products made from wood. Several studies related to the resistance of wood and non-wood lignocellulosic materials have been carried out by researchers, including [6][7][8][9]. Termite attacks are a risk for particleboard, a composite product consisting of lignocellulosic material.…”
Section: Introductionmentioning
confidence: 99%
“…It is due to the extractive content and the low density of the wood. The research results of Iswantu et al [2] and Hadi et al [3] showed that some tropical woods, such as Styrax sumatrana, Anthocephalus cadamba, Falcataria moluccana, Acacia mangium, Pinus merkusii, have low resistance to attack by subterranean termites. According to Shanbhag et al [4], cellulose has a positive correlation to the durability of wood, while lignin and total phenolic compounds have a negative correlation to the durability of wood.…”
Section: Introductionmentioning
confidence: 99%